2015
DOI: 10.3390/antiox4040768
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Effects of DL-Alpha-Tocopherol Supplementation on Oxidative Damage, Total Antioxidant Protection and the Sex-Specific Responses of Reproductive Effort and Lifespan to Dietary Manipulation in Australian Field Crickets (Teleogryllus commodus)

Abstract: The oxidative stress theory predicts that the accumulation of oxidative damage causes aging. More generally, oxidative damage could be a cost of reproduction that reduces survival. Both of these hypotheses have mixed empirical support. To better understand the life-history consequences of oxidative damage, we fed male and female Australian field crickets (Teleogryllus commodus) four diets differing in their protein and carbohydrate content, which have sex-specific effects on reproductive effort and lifespan. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 64 publications
2
16
0
Order By: Relevance
“…The angles between the linear vectors describe the relative differences in the performance between two traits with respect to the consumption of protein, carbohydrate and micronutrients. A smaller angle implies that the two traits tend to show similar expression in a similar location in the nutritional landscape, whereas a large angle would imply a conflict between the two traits during allocation of nutrients (Archer et al, ; Rapkin et al, ). With angles less than 40°, the optima for courtship song PC1, CHC PC1 and CHC PC2 resided close together in the nutritional landscape; Figure shows that the three traits were located in the region of high P:C ratio.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The angles between the linear vectors describe the relative differences in the performance between two traits with respect to the consumption of protein, carbohydrate and micronutrients. A smaller angle implies that the two traits tend to show similar expression in a similar location in the nutritional landscape, whereas a large angle would imply a conflict between the two traits during allocation of nutrients (Archer et al, ; Rapkin et al, ). With angles less than 40°, the optima for courtship song PC1, CHC PC1 and CHC PC2 resided close together in the nutritional landscape; Figure shows that the three traits were located in the region of high P:C ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Although courtship song was found to be more metabolically expensive than calling song (Hack, ), the extended duration of calling song necessitates a greater amount of energy that would be provided by a high‐carbohydrate diet. Calling effort has previously been measured as the total time a male spent calling (Archer et al, ; Maklakov et al, ; Rapkin et al, ). In contrast, we assayed the temporal structure of the courtship song, finding song quality to be maximized by high‐P:C diets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Male crickets provided with greater access to nutritional resources have been shown to expend more energy on calling song than males with limited nutritional resources (Hunt et al, 2004), and the availability of protein in the diet has been found to underlie a resource allocation trade-off between calling song and lifespan in the congeneric cricket Teleogryllus commodus (Maklakov et al, 2008). Male T. commodus fed diets that stimulated increased energetic expenditure on calling song were found to have elevated levels of protein oxidation in whole-body lysates (Archer et al, 2015). However, dietary supplementation with vitamin E did not affect protein oxidation or antioxidant capacity (Archer et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Male T. commodus fed diets that stimulated increased energetic expenditure on calling song were found to have elevated levels of protein oxidation in whole-body lysates (Archer et al, 2015). However, dietary supplementation with vitamin E did not affect protein oxidation or antioxidant capacity (Archer et al, 2015).…”
Section: Discussionmentioning
confidence: 99%